ANALISIS KEKUATAN LANDASAN ALUMINIUM PADA PERANGKAT BRAKITERAPI MEDIUM DOSERATE - Rahmat Rahmat; Ari Satmoko (BATAN, 2012)
A STRENGHT ANALYSIS OF THE ALUMINiUM ANVIL OF THE MEDIUM DOSE RATE (MDR) BRACHYTHERAPHY EQUIPMENT. A strenght analysis of the aluminium anvil of the medium dose rate (MDR) brachytheraphy equipment has ben performed. The analysis is to evaluate the strenght of anvil structure used in brachytheraphy equipmen. The anvil serves to connect the wire driver module, the source container module and the channels distributor module. The method is to analyze stresses by using mathematical model. The analysis shows that the aluminium anvil has the largest stress at 6,676 N/mm2 and it is still under the yeild stress at 199,73 N/mm2 . Evaluation results of the structure analysis can be used in designing the anvil for MDR brachytheraphy equipment. ANALISIS KEKUATAN LANDASAN ALUMINIUM PADA PERANGKAT BRAKITERAPI MEDIUM DOSERATE (MDR). Telah dilakukan analisis kekuatan landasan aluminium pada perangkat Brakiterapi medium doserate (MDR). Analisis dilakukan untuk mengetahui kekuatan struktur landasan perangkat brakiterapi. Landasan berfungsi menghubungkan modul penggerak sling, modul container sumber dan modul distributor chanel. Metode yang dilakukan adalah menganalisis tegangan dengan menggunakan pemodelan matematika. Dari analisis diperoleh bahwa nilai tegangan stress sebesar 6,676 N/mm2 masih jauh dibawah nilai yield sebesar 199,73 N/mm2. Hasil evaluasi dari analisis pada struktur tersebut dapat digunakan dalam desain landasan untuk perangkat brakiterapi MDR